Handbook of action research : the concise paperback edition - Bradbury, Hilary; Reason, Peter (SAGE, 2006)
With the Handbook of Action Research hailed as a turning point in how action research is framed and understood by scholars, this paperback edition of the First Edition has been structured to provide an easy inroad into the field for researchers and students. It includes concise chapter summaries and an informative introduction that draws together the different strands of action research and reveals their diverse applications as well as their interrelations.